2020
DOI: 10.31557/apjcp.2020.21.11.3393
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Enhances the Anti-inflammatory Effect of Tumor- Infiltrating CD33+11b+HLA-DR Myeloid-Derived Suppressor Cells in Gastric Cancer: A Possible Relation to MicroRNA-494

Abstract: Background: Accumulation of myeloid-derived suppressor cells (MDSCs) constitutes a key mechanism of tumor immune evasion in gastric cancer (GC). Therefore, searching for more accurate prognostic factors affecting their immunosuppressive role has become a growing interest in cancer immunotherapy research. Increased expression of microRNA-494 was noticed in MDSCs from tumor-bearing mice, suggesting another new therapeutic objective for cancer treatment. It was also discovered that tumor-derived transforming grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Expansion of MDSCs was associated with resistance to treatment and poor prognosis in malignant tumors (246). In GC patients, the levels of MDSCs was associated with cancer stage and survival (248), such that higher levels of MDSCs were associated with later tumor stage and poor prognosis (249)(250)(251), as well as with higher mortality and risk of tumor recurrence and progression. In addition, patients with high MDSCs levels had significantly shorter OS than patients with low MDSC levels in patients with stage IV gastrointestinal cancer (252).…”
Section: Therapeutic Strategies Targeting Mdscsmentioning
confidence: 99%
“…Expansion of MDSCs was associated with resistance to treatment and poor prognosis in malignant tumors (246). In GC patients, the levels of MDSCs was associated with cancer stage and survival (248), such that higher levels of MDSCs were associated with later tumor stage and poor prognosis (249)(250)(251), as well as with higher mortality and risk of tumor recurrence and progression. In addition, patients with high MDSCs levels had significantly shorter OS than patients with low MDSC levels in patients with stage IV gastrointestinal cancer (252).…”
Section: Therapeutic Strategies Targeting Mdscsmentioning
confidence: 99%
“…These four miRNAs are associated with the induction of MDSCs and Th17 cells through cytokines TGFB1, IL-6 and IL-17, resulting in the immune suppression of DLBCL ( 58 ). In gastric cancer, miR-494 is positively associated with the expression of tumor-derived TGF-β which exaggerates the suppressive roles of MDSCs ( 49 ). In various tumor mouse models (such as lung cancer, breast cancer and colon cancer), it has been found that the tumor-derived factor GM-CSF induces miR-200c overexpression to activate Akt by negatively regulating the transcriptional regulator friend of Gata 2 (FOG2) and PTEN expression, further enhancing the immunosuppressive activity of MDSCs ( 59 ) ( Table 1 ).…”
Section: Post-transcriptional Regulation Of Tumor Mdscs With Mirnas/l...mentioning
confidence: 99%
“…Myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs) recruited to the primary and secondary tumor sites contribute to the immunosuppressive environment. They are recruited in response to numerous growth factors, chemokines, and cytokines that are secreted by the cancer cells and other stromal cells ( 137 - 141 ). Through different mechanisms, MDSCs and Tregs negatively affect the antitumor activity of NK cells and prevent tumor infiltration of antitumor cytotoxic CD8 + T cells ( 139 , 142 ).…”
Section: Targeting Key Mediators Of Metastasis By Aptamer-based Thera...mentioning
confidence: 99%